Study on the effect of insemination time on pregnancy rate of Bangladeshi buffalo in intensive farming (SAARC Journal of Agriculture, 2019)
The study was designed to evaluate the insemination time and pregnancy rate of Bangladeshi buffalo at Lal Teer Livestock Breeding and Research Farm, Bhaluka, Mymensingh, Bangladesh during January 2017 to June 2018. A total of 30 cyclic buffaloes were included in this study. The animals were inseminated under four different times, i.e. inseminated i) between 0-6 hours after seeing first sign of estrous, ii) between 6-12 hours after seeing first sign of estrous, iii) between 12-18 hours after seeing first sign of estrous and v) between 18-24 hours after seeing first sign of estrous. The pregnancies (positive or negative) were confirmed by rectal palpation and transrectal ultrasonography after 60 days of artificial insemination (AI). The total pregnant animals in this study were 40%. The highest pregnancy rate (60%) was observed in insemination between 12-18 hours after seeing first sign of estrous and the lowest pregnancy rate (0%) was observed in insemination between 0-6 hours after seeing first sign of estrous. The findings of the study suggest that, the conception rate of buffalo depend on the time of AI, detection of proper estrus symptoms and site of semen deposition.SAARC J. Agri., 16(2): 143-152 (2018)